Endangered [large type] - Box, C. J. (Box, C. J. Joe Pickett novel., 2015)
"When Wyoming game warden Joe Pickett's eighteen-year-old ward runs away with Dallas Cates and then is found in a ditch barely alive, Joe believes Cates is responsible. But Cates claims that she ran away from him too and evidence points to another man. Joe is determined to find the truth, even if it kills him"--